Automotive industry in Slovakia as a driver of economic growth and development - Zvarková, Zuzana; Frömmel, Tomáš; Špecián, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
The aim of this work is to prove the mutual relationship and dependence between the Automotive industry and the Slovak economy. First half of practical part calculates cor- relation coefficients between five potential bonds of individual performance indicators (e.g. Revenues of car manufacturers and Slovak nominal GDP). Strong correlation coefficients between these bonds prove that there is a significant mutual relationship and strong dependence. Second half of practical part presents very comprehensive SWOT analysis of the automotive industry in Slovakia. The aim of the analysis is to emphasize the strong two-way relationship. Additionally, to propose, how could the automotive industry accelerate the Slovak economy if influenced properly and how it could overcome upcoming threats that could have a negative impact on the economy of the country.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses